An Electrochemical Study of the Effect of High Salt Concentration on Uniform Corrosion of Carbon Steel in Aqueous CO2 Solutions. Issue 5 (30th April 2021) - Madani Sani, Fazlollah; Brown, Bruce; Nesic, Srdjan
Abstract : Uniform C O 2 corrosion of carbon steel facilities is often a major problem when handling produced water in the oil and gas fields. High amounts of dissolved salts are often present in produced water. A limited number of research studies has been conducted on the effect of salt concentration on uniform C O 2 corrosion. In this study, the effect of NaCl concentration on uniform C O 2 corrosion of X65 carbon steel was investigated in C O 2 saturated aqueous solutions using a rotating cylinder system at 30 °C, autogenous pH, and 1 bar total pressure in an NaCl concentration range of 0‒4.27 molality (m) (0‒20 wt.%). With increasing NaCl concentration, the corrosion rate increased sharply and reached its maximum value at ∼0.17 m (1 wt.%) NaCl and then decreased with further increase in NaCl concentration. The observed trend in the corrosion rate with increasing NaCl concentration was primarily a consequence of the change in the cathodic limiting current density, which was the main factor controlling the rate of the overall corrosion process. The additional factor was the change in the rate of the anodic reaction with salt concentration.